In Vitro and In Vivo Evaluation of Staphylococcal Superantigen Peptide Antagonists - Rajagopalan, Govindarajan (American Society for Microbiology, 2004)
Superantigen peptide antagonists failed to block T-cell activation and cytokine production as well as toxic shock induced by staphylococcal enterotoxin B (SEB) in HLA class II transgenic mice. They also failed to inhibit the binding of SEB to HLA class II molecules as well as activation of human T lymphocytes in vitro.